Fabricating printed circuit boards - Varteresian, Jon
Jon Varteresian is owner of JV Enterprises, a company specializing in the design and manufacture of printed circuit boards. He offers numerous tips and techniques from his years of experience that guarantee a smooth and painless PC board design and fabrication process using his step by step approach. Numerous illustrations and photographs demonstrate each step of the process. Topics covered in the book include: safety issues, schematic capture, circuit placement and routing, making printed circuit boards, and plans for projects. An extensive resource list and glossary are also provided.